Distinct Domains of Erythroid Krüppel-Like Factor Modulate Chromatin Remodeling and Transactivation at the Endogenous β-Globin Gene Promoter - Brown, R. Clark (American Society for Microbiology, 2002)
Characterization of the mechanism(s) of action of trans-acting factors in higher eukaryotes requires the establishment of cellular models that test their function at endogenous target gene regulatory elements. Erythroid Krüppel-like factor (EKLF) is essential for β-globin gene transcription. To elucidate the in vivo determinants leading to transcription of the adult β-globin gene, functional domains of EKLF were examined in the context of chromatin remodeling and transcriptional activation at the endogenous locus. Human EKLF (hEKLF) sequences, linked to an estrogen-responsive domain, were studied with an erythroblast cell line lacking endogenous EKLF expression (J2eΔeklf). J2eΔeklf cells transduced with hEKLF demonstrated a dose-dependent rescue of β-globin transcription in the presence of inducing ligand. Further analysis using a series of amino-terminal truncation mutants of hEKLF identified a distinct internal domain, which is sufficient for transactivation. Interestingly, studies of the chromatin structure of the β-promoter revealed that a smaller carboxy-terminal domain generated an open promoter configuration. In vitro and in vivo binding studies demonstrated that this region interacted with BRG1, a component of the SWI/SNF chromatin remodeling complex. However, further study revealed that BRG1 interacted with an even smaller domain of EKLF, suggesting that additional protein interactions are required for chromatin remodeling at the endogenous β-promoter. Taken together, our findings support a stepwise process of chromatin remodeling and coactivator recruitment to the β-globin promoter in vivo. The J2eΔeklf inducible hEKLF system will be a valuable tool for further characterizing the temporal series of events required for endogenous β-globin gene transcription.